The Struggles Of The Low-Caste Untouchables In The God Of Small Things In Navigating Crisis Of Modernity - Nurjanah, Fitri; Istiani, Imas (Makassar State University, 2025)
The God of Small Things by Arundhati Roy depicts in depth the crisis of modernity faced by the lower caste Untouchables, primarily through the character of Velutha. Modernity itself is an emerging value in a society that is associated with domination over irrationality. The main conflict at issue in this research is the clash that occurs in traditional Indian society represented by the upper-caste, Touchable, and the low-caste, Untouchable. Caste discrimination as a form of conflict is still deeply embedded in Indian society. The low caste, commonly referred to as Untouchables, experience many difficulties in their struggle for identity and in rationalizing thoughts that are constrained by the culture of society that continues to view them with the stigma of lower caste. The struggle of the Untouchables against the power structure at that time was divided into several difficult phases, such as the case of Velutha's forbidden relationship with an upper caste named Ammu. Thus, it was found that the main enemy in their struggle was the social norms of the society itself. The conclusion was that the conflict between tradition and modernity remained deeply rooted, and hopes for change and equality failed to be achieved. This is the final finding of this research, named a crisis of modernity. The implication is the need to continue to fight for individual rights and against all forms of discrimination, as well as supporting social change that is equitable for all.